Policy Implementation of the Work Discipline Of Civil Servants (Study Did At North Sulawesi Provincial Health Office) - Lompoliuw, Nicky; Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThis research thesis is prepared in order to obtain a Bachelor’s degree in The Faculty of Social and Political Sciences, University of Sam Ratulangi Manado. Based on the preliminary study conducted by the researcher, the low awareness of civil servants in the implementation of labor discipline policies in the scope of the civil servants health bureau of north Sulawesi province that has been set in accordance to PP no 53 of 2010, on discipline of civil servants. This the research discovered a need to review and reconsider the policy implementation on labor discipline of the civil servants in north Sulawesi provincial health bureau. This study used qualitative research methods. Date were collected from the stage of observation, interview, to documentation.The conclusion that can be drawn from this research is that the civil servants in north Sulawesi provincial health bureau still have low awareness on the importance of discipline improve the quality of their work. In the other words, they can improve the quality of public service provided to the communities in need.Keywords : Policy Implementation, Employee Work Discipline.